2022
DOI: 10.3390/polym14102070
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium officinale Enzyme Changing the Structure and Behaviors of Chitosan/γ-poly(glutamic acid) Hydrogel for Potential Skin Care

Abstract: Hydrogels have been widespreadly used in various fields. But weak toughness has limited their further applications. In this study, Dendrobium officinale enzyme (DOE) was explored to improve chitosan/γ-poly(glutamic acid) (CS/γ-PGA) hydrogel in the structure and properties. The results indicated that DOE with various sizes of ingredients can make multiple noncovalent crosslinks with the skeleton network of CS/γ-PGA, significantly changing the self-assembly of CS/γ-PGA/DOE hydrogel to form regular protuberance n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…However, these limitations can be effectively addressed by modifying the physical and chemical properties and functions of CS/γ-PGA hydrogel. In 2022, Wang et al explored a multi-step non-covalent crosslinking strategy for CS/γ-PGA hydrogel by incorporating Dendrobium candidum enzyme (DOE) ( Figure 4 B) [ 36 ]. They discovered that an increase in γ-PGA content and the addition of DOE resulted in a hydrogel with higher porosity, significantly enhancing its hydrophilicity and water retention.…”
Section: The γ-Pga Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these limitations can be effectively addressed by modifying the physical and chemical properties and functions of CS/γ-PGA hydrogel. In 2022, Wang et al explored a multi-step non-covalent crosslinking strategy for CS/γ-PGA hydrogel by incorporating Dendrobium candidum enzyme (DOE) ( Figure 4 B) [ 36 ]. They discovered that an increase in γ-PGA content and the addition of DOE resulted in a hydrogel with higher porosity, significantly enhancing its hydrophilicity and water retention.…”
Section: The γ-Pga Hydrogelmentioning
confidence: 99%
“… ( A ) The porous structure of hydrogels formed by different PH regulators, different γ-PGA contents, and different drying methods [ 35 ]. ( B ) Effect of DOEs on CS/γ-PGA hydrogel [ 36 ]. ( C ) Preparation principle of HA/γ-PGA [ 41 ].…”
Section: The γ-Pga Hydrogelmentioning
confidence: 99%
“…12 Dendrobium nobile polysaccharide plays a crucial role in shielding skin fibroblasts from UVA-induced photoaging 13 and regulating immune cells to mitigate skin inflammation. 14 While recognized for cosmetic benefits, [15][16][17][18][19] Although some studies have explored the potential of Dendrobium ironum for skin repair, there remains a scarcity of specific research regarding its role in promoting wound healing. This knowledge gap highlights the need for further research to unravel the potential of Dendrobium as a wound healing-promoting medicine.…”
Section: Introductionmentioning
confidence: 99%
“…However, most hydrogels possess uneven crosslinking networks constructed with natural macromolecules, without any effective energy dissipation mechanism preventing possible crack propagation or stress concentration. On this account, dendrobium officinale enzyme (DOE) was proposed to improve the structural uniformity and the toughness of chitosan/γ-poly(glutamic acid) (CS/γ-PGA) hydrogel [ 20 ]. The results indicated that DOE with various amounts of ingredients can make multiple noncovalent crosslinks with the skeleton network of CS/γ-PGA, significantly changing the self-assembly of CS/γ-PGA/DOE hydrogel to form regular protuberance nanostructures, exhibiting stronger toughness and better behaviors for skin care.…”
mentioning
confidence: 99%